Chronic liver disease and active hepatitis C virus infection in patients with antibodies to this virus. Issue 2 (February 1994) - Petrelli, E; Manzin, A; Paolucci, S; Cioppi, A; Brugia, M; Muretto, P; Clementi, M
Abstract : AIMS–To assess the association between active hepatitis C virus (HCV) infection and liver damage in randomly selected patients with antibodies to the virus. METHODS–Thirty three consecutive subjects with serologically confirmed positivity for antibodies to HCV were studied for the presence of liver and circulating viral sequences by using the reverse transcription polymerase chain reaction (RT-PCR) and specific primers for the 5'-untranslated region (5'-UTR) of the HCV genome. Parallel clinical, biochemical, and histological investigations were carried out in all cases. RESULTS–A comparative virological and histological investigation showed the presence of molecular signs of active viral replication and different degrees of liver damage in all cases. Baseline values of liver and plasma samples from all the patients showed (with one exception) the presence of detectable HCV RNA sequences, despite alanine amino transferase activities being within normal values or within 1.5 times the upper limit of normal in 13 of them. Examination of percutaneous liver biopsy specimens showed the presence of confirmed liver damage (ranging from chronic persistent hepatitis to cirrhosis) in all 33 patients. CONCLUSIONS–Circulating HCV RNA sequences (a direct sign of active HCV infection) are associated with liver damage, even in the absence of clinical or biochemical signs of overt liver disease. Parallel molecular, histological, and clinical follow up of these patients is needed to understand precisely the natural history of HCV infection and for correct clinical management.